Modeling of Frontotemporal Dementia Using iPSC Technology - Kim, Minchul; Kim, Hee Jin; Koh, Wonyoung; Li, Ling; Heo, Hyohoon; Cho, Hanna; Lyoo, Chul Hyoung; Seo, Sang Won; Kim, Eun-Joo; Nakanishi, Mahito; Song, Jihwan (International journal of molecular sciences, 2020)
Frontotemporal dementia (FTD) is caused by the progressive degeneration of the frontal and temporal lobes of the brain. Behavioral variant FTD (bvFTD) is the most common clinical subtype of FTD and pathological subtypes of bvFTD are known as FTD-tau, transactive response (TAR) DNA-binding protein 43 (TDP-43), and fused in sarcoma (FUS). Pathological mechanisms of bvFTD are largely unknown. In this study, we investigated the expression of pathological markers, such as p-Tau, TDP-43, and FUS, in the induced pluripotent stem-cell-derived neurons (iPSN) from two sporadic bvFTD patients and one normal subject. We also used an FTD-patient-derived iPSC-line-carrying microtubule-associated protein tau (MAPT) P301L point mutation as positive control for p-Tau expression. Staurosporine (STS) was used to induce cellular stress in order to investigate dynamic cellular responses related to the cell death pathway. As a result, the expression of active caspase-3 was highly increased in the bvFTD-iPSNs compared with control iPSNs in the STS-treated conditions. Other cell-death-related proteins, including Bcl-2-associated X protein (Bax)/Bcl-2 and cytochrome C, were also increased in the bvFTD-iPSNs. Moreover, we observed abnormal expression patterns of TDP-43 and FUS in the bvFTD-iPSNs compared with control iPSNs. We suggest that the iPSC technology might serve as a potential tool to demonstrate neurodegenerative phenotypes of bvFTD, which will be useful for studying pathological mechanisms for FTD as well as related drug screening in the future.